2017
DOI: 10.1007/s12602-017-9321-7
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Lactobacillus acidophilus to Thermal Stress Yields a Thermotolerant Variant Which Also Exhibits Improved Survival at pH 2

Abstract: Loss in probiotic viability upon exposure to stressful storage and transport conditions has plagued the probiotic market worldwide. Lactobacillus acidophilus is an important probiotic that is added to various functional foods. It is known to be fairly labile and susceptible to temperature variations that it encounters during processing and storage which increases production cost. It has been repeatedly demonstrated that pre-exposure to sub-lethal doses of stress, particularly, temperature and pH, leads to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…adaptation did little to enhance the acid tolerance, which is similar to the results reported by Chen et al (2017) and is different from Kulkarni et al (2018). The results illustrated that acid adaptation can be used as a potential strategy to improve cell survival in response to multiple lethal stresses.…”
Section: Effects Of Cross-protection On the Stress Tolerance L Plantsupporting
confidence: 76%
“…adaptation did little to enhance the acid tolerance, which is similar to the results reported by Chen et al (2017) and is different from Kulkarni et al (2018). The results illustrated that acid adaptation can be used as a potential strategy to improve cell survival in response to multiple lethal stresses.…”
Section: Effects Of Cross-protection On the Stress Tolerance L Plantsupporting
confidence: 76%
“…One of the stress responses of LAB is heat-related stress (Chang-Ho et al, 2015). Kulkarni et al (2018) reported that Lactobacillus acidophilus could survive at 65℃ for 40 min and exhibited a positive correlation between the synthesis and induction of heat shock proteins (HSPs). The up-regulation of HSPs, including the chaperonins (DnaK and GroEL) and cofactors (GroES), is the main adaptation for the enhanced heat resistance of LAB.…”
Section: Heat Shockmentioning
confidence: 99%
“…We have demonstrated that the newly developed L. acidophilus EG008 strain had better thermal resistance than wild type at high temperatures of 65-75 • C (Figure 2B). Recently, studies on the development of EG008 strains using ALE have been conducted (Kulkarni et al, 2018;Min et al, 2020), but most of the experiments were performed at temperatures below 65 • C to ensure applicability in LTST pasteurization (Vaudagna et al, 2002). Therefore, the EG008 strain developed in this study is expected to be utilized for HTST pasteurization, which sterilizes at a relatively high temperature.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the thermal resistance of L. acidophilus LA1-1 was measured at 37-58 • C (Kim et al, 2001). There have also been attempts to develop L. acidophilus EG008 strains using ALE such as L. acidophilus NCFM at 65 • C (Kulkarni et al, 2018) and Lactiplantibacillus plantarum Lp 998 at 45-55 • C (Ferrando et al, 2015).…”
Section: Introductionmentioning
confidence: 99%